GCKR and PPP1R3B identified as genome‐wide significant loci for plasma lactate: the Atherosclerosis Risk in Communities (ARIC) study. Issue 7 (30th October 2015) - Tin, A.; Balakrishnan, P.; Beaty, T. H.; Boerwinkle, E.; Hoogeveen, R. C.; Young, J. H.; Kao, W. H. L.
Abstract: Aim: To investigate the genetic influence of circulating lactate level, a marker of oxidative capacity associated with diabetes. Methods: We conducted a genome‐wide association study of log‐transformed plasma lactate levels in 6901 European‐American participants in the Atherosclerosis Risk in Communities study. For regions that achieved genome‐wide significance in European‐American participants, we conducted candidate region analysis in African‐American subjects and tested for interaction between metformin use and the index single nucleotide polymorphisms for plasma lactate in European‐American subjects. Results: The genome‐wide association study in European‐American subjects identified two genome‐wide significant loci, GCKR (rs1260326, T allele β=0.08; P =1.8×10 ‐47 ) and PPP1R3B/LOC157273 (rs9987289, A allele β=0.06; P =1.6×10 ‐9 ). The index single nucleotide polymorphisms in these two loci explain 3.3% of the variance in log‐transformed plasma lactate levels among the European‐American subjects. In the African‐American subjects, based on a region‐significant threshold, the index single nucleotide polymorphism at GCKR was associated with plasma lactate but that at PPP1R3B/LOC157273 was not. Metformin use appeared to strengthen the association between the index single nucleotide polymorphism at PPP1R3B/LOC157273 and plasma lactate in European‐American subjects ( P for interaction=0.01). Conclusions: We identified GCKR and PPP1R3B/LOC157273 as two genome‐wide significant loci of plasma lactate. Both loci are associated with other diabetes‐related phenotypes. These findings increase our understanding of the genetic control of lactate metabolism. What's new?: We report the first genome‐wide association study of plasma lactate levels in individuals with European ancestry and the identification of GCKR and PPP1R3B as genome‐wide significant loci of lactate levels. The association at GCKR was also significant in individuals of African ancestry at the gene level. We also identified a significant interaction between metformin and the index single nucleotide polymorphism at PPP1R3B on lactate levels. Our findings add to our knowledge on the mechanism of metformin and lactate metabolism.